BS EN ISO 6887-1 AMD 1. Microbiology of the food chain. Preparation of test samples, initial suspension and decimal dilutions for microbiological examination. Part 1. General rules for the preparation of the initial suspension and decimal dilutions (31st July 2023) - British Standards Institution,
No abstract available